1988
DOI: 10.1007/bf02180022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a low to middle tar/medium nicotine cigarette designed to maintain nicotine delivery to the smoker

Abstract: A specific objective of this 6-week crossover study was to determine how 21 regular smokers of middle tar cigarettes changed their smoking behaviour and uptake of smoke constituents, when switching to either lower tar cigarettes capable of delivering amounts of nicotine similar to a conventional middle tar cigarette (maintained nicotine product), or to conventional low tar/low nicotine cigarettes. Subjects visited the laboratory every 2 weeks for detailed assessment of their smoking behaviour. Weekly per capit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…(ii) Studies which investigated the impact of a significant reduction in the nicotine content on smoking behaviour, termed here as 'RNC studies'. In Supplementary data No 2, Table D, data from 19 non-RNC studies 5 are listed (Armitage et al, 1988;Benowitz et al, 1982Benowitz et al, , 1986Benowitz et al, , 2005Benowitz et al, , 2009Fagerström, 1982;Feng et al, 2006;Frost et al, 1995;Guyatt et al, 1989;Haley et al, 1985;Hammond et al, 2005;Kolonen et al, 1988;McAdam et al, 2011;Robinson et al, 1982Robinson et al, , 1983Roethig et al, 2005Roethig et al, , 2007Russell et al, 1982;Shepperd et al, 2011;Zacny and Stitzer, 1988), for which CIs were calculated by applying formulae (2e) and (5). In addition, Table D lists four RNC studies (Benowitz et al, , 2007(Benowitz et al, , 2012Hatsukami et al, 2010), for which nicotine biomarker-based CIs were calculated using formula (2e).…”
Section: Meta-analysis Of Brand-switching Studiesmentioning
confidence: 99%
“…(ii) Studies which investigated the impact of a significant reduction in the nicotine content on smoking behaviour, termed here as 'RNC studies'. In Supplementary data No 2, Table D, data from 19 non-RNC studies 5 are listed (Armitage et al, 1988;Benowitz et al, 1982Benowitz et al, , 1986Benowitz et al, , 2005Benowitz et al, , 2009Fagerström, 1982;Feng et al, 2006;Frost et al, 1995;Guyatt et al, 1989;Haley et al, 1985;Hammond et al, 2005;Kolonen et al, 1988;McAdam et al, 2011;Robinson et al, 1982Robinson et al, , 1983Roethig et al, 2005Roethig et al, , 2007Russell et al, 1982;Shepperd et al, 2011;Zacny and Stitzer, 1988), for which CIs were calculated by applying formulae (2e) and (5). In addition, Table D lists four RNC studies (Benowitz et al, , 2007(Benowitz et al, , 2012Hatsukami et al, 2010), for which nicotine biomarker-based CIs were calculated using formula (2e).…”
Section: Meta-analysis Of Brand-switching Studiesmentioning
confidence: 99%
“…However, some researchers have studied the independent effects of tar and nicotine yields and have concluded that the tar yield of a cigarette is an important determiner of smoking behaviour (Stepney et al 1981;Sutton et al 1982;Armitage et al 1988;Fairweather 1989;Hasenfratz et al 1993;Baldinger et al 1995). It has been hypothesised that that some components of tar have sensory properties and smokers may smoke more intensely to compensate for a reduction in the sensory properties of lower tar cigarettes (Stepney 1981;Hasenfratz et al 1993).…”
Section: Introductionmentioning
confidence: 96%
“…These studies used either a between-subject design comparing different products (56, 61, 7078), within-subject design taking assessments during usual brand cigarette smoking and after switching to a product (7981) or within-subject cross-over design with different products (23, 8285). Subjects were required to use a specific product (61, 70, 7283, 8589), or were given a choice after sampling the products (56, 71). Some of these studies included additional or different experimental design features.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these studies examined the effects of cigarettes with different nicotine or tar yields (7071, 73, 7678, 8485, 8789) or different amounts of product use (83). The duration in trials ranged from 2 weeks to 13 months.…”
Section: Resultsmentioning
confidence: 99%